2020
DOI: 10.3390/molecules25204602
|View full text |Cite
|
Sign up to set email alerts
|

Nanohydroxyapatite-Mediated Imatinib Delivery for Specific Anticancer Applications

Abstract: In the present study, a nanoapatite-mediated delivery system for imatinib has been proposed. Nanohydroxyapatite (nHAp) was obtained by co-precipitation method, and its physicochemical properties in combination with imatinib (IM) were studied by means of XRPD (X-ray Powder Diffraction), SEM-EDS (Scanning Electron Microscopy-Energy Dispersive X-ray Spectroscopy), FT-IR (Fourier-Transform Infrared Spectroscopy), absorption spectroscopy as well as DLS (Dynamic Light Scattering) techniques. The obtained hydroxyapat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…This observation was also noted in our previous paper regarding the nanoapatite-mediated delivery system for imatinib. 28 Second, in the hydrogel in which hydroxyapatite was dispersed, distinct peaks derived from nHAp were seen at 2θ equal to 25.5, 28.3, 29.1, 31.4, 32.5, 33.7, 39.3, 46.2, 49.1, and 52.6°. Moreover, all peaks observed in the nHAp/IM/galactose hydrogel and nHAp correspond to the peak position for the theoretical hexagonal hydroxyapatite (ICSD−26204 29 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This observation was also noted in our previous paper regarding the nanoapatite-mediated delivery system for imatinib. 28 Second, in the hydrogel in which hydroxyapatite was dispersed, distinct peaks derived from nHAp were seen at 2θ equal to 25.5, 28.3, 29.1, 31.4, 32.5, 33.7, 39.3, 46.2, 49.1, and 52.6°. Moreover, all peaks observed in the nHAp/IM/galactose hydrogel and nHAp correspond to the peak position for the theoretical hexagonal hydroxyapatite (ICSD−26204 29 ).…”
Section: Resultsmentioning
confidence: 97%
“…A similar observation was found in our previous research concerning time-dependent fluconazole release from the galactose hydrogels loaded and unloaded with nHAp . Moreover, the nHAp nanoparticle-mediated imatinib system was also tested previously, revealing that 100% of IM was achieved in PBS after 45 min of nHAp/IM incubation and 88% of the drug was released during the first 5 min . In this study, 60% of the drug was released after 5 min of experimental time.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In particular, Sobierajska et al [ 99 ] prepared nanoparticles of hydroxyapatite (nHAp, Ca 10 (PO 4 ) 6 (OH) 2 ), whose physicochemical properties were studied by means of XRPD (X-ray Powder Diffraction), SEM–EDS (Scanning Electron Microscopy–Energy Dispersive X-ray Spectroscopy), FT-IR (Fourier-Transform Infrared Spectroscopy) and DLS (Dynamic Light Scattering) techniques. During the preparation of this nanocarrier drug, a conversion from crystalline to amorphous form occurred, contributing to its better solubility and higher dissolution rate in body fluids, improving drug bioavailability.…”
Section: Nanoparticles Of Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…[24] Apart from being simple drug vehicles, nHAP also possesses antitumor activities both in vitro and in vivo. [25,26] Recently, it has been shown that nHAP significantly inhibits the proliferation of different types of cancer cells, such as hepatoma, gastric cancer, colon cancer, melanoma, breast cancer and glioma cells. [27] Figure 2 depicts the application of nHAP in inhibiting tumor.…”
Section: Introductionmentioning
confidence: 99%